Indigenous peoples and the challenges of accessing the right to health as a way of preventing conflicts in the judiciary and the achievement of citizenship (Revista Brasileira Multidisciplinar, 2025)
This article explores the challenges faced by indigenous peoples in Brazil in accessing the right to health, guaranteed constitutionally and by international treaties. Although the creation of the Indigenous Health Care Subsystem by Law 9,836/1999 represents a legislative advance, practical application still faces difficulties. Among the main obstacles are the precariousness of health infrastructure, the lack of financial resources, the absence of efficient public policies and the devastation caused by illegal activities, such as mining and deforestation. The study uses a qualitative approach and the deductive method to evaluate how important these factors are in maintaining the health crisis in indigenous communities. The analysis suggests that, in addition to greater government commitment, a more humanized and sensitive approach to the cultural and geographic specificities of this population is necessary to guarantee the full exercise of the right to health and the promotion of citizenship.
Keywords: Citizenship; Conflict management; Rights to health; Dignity of the Human Person; The Judiciary